Analisis Kelayakan Finansial Usahatani Wortel UD Gizi Wortel Di Kabupaten Semarang - ardiyanto, meiwan kris (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
The overuse of production factors will increase production costs, which at the end will reduce farming income if the additional costs incurred are higher than the additional income. In the agriculture that case known as The Law of Deminishing Return. Therefore, this research aims to know to analyze the financial feasibility of carrots farming at the UD Gizi Wortel. This research was done on May 2019 until Jule 2019 at the UD. Gizi Wortel, located in the village of Jimbaran, Bandungan Sub-district, Semarang Regency. This research is using qualitative approach. The technique used for taking the sample is purposive sampling and the amount of the sample that used is just one respondent which is the owner of UD. Gizi Wortel. The analytic data that used for this research is financial feasibility analysis with BEP (Break Even Point) and R/C ratio. The results of this research showed that the financial feasibility analysis of UD. Gizi Wortel is having production BEP of 1.788 kg every planting season, BEP price of Rp 4,470 per kg, an R/C ratio of 2.4, so the bussiness is feasible to be carried out.